Bilateral vocal cord palsy as complication of CNS tuberculosis - Liesa Regner-Nelke; Bendix Labeit; Christopher Nelke; Wolfram Schwindt; Rainer Dziewas; Sonja Suntrup-Krueger (BMC Neurology, 2023)
Abstract Background Tuberculous meningitis, a rare but severe form of extrapulmonary tuberculosis, frequently affects cranial nerves. While nerves III, VI and VII are commonly involved, involvement of caudal cranial nerves is rarely described. Here, we report a rare case of bilateral vocal cord palsy secondary to caudal cranial nerve involvement in tuberculous meningoencephalitis, that occurred in Germany, a country with low tuberculosis incidence. Case presentation A 71-year-old woman was transferred for further treatment of hydrocephalus as a complication of presumed bacterial meningitis with unknown pathogen at that time. Because of decreased consciousness, intubation was performed and an empiric antibiotic therapy with ampicillin, ceftriaxone and acyclovir was initiated. Upon admission to our hospital, an external ventricular drainage was placed. Cerebrospinal fluid analysis revealed Mycobacterium tuberculosis as the causative pathogen, and antitubercular treatment was initiated. Extubation was possible one week after admission. Eleven days later, the patient developed inspiratory stridor that worsened within a few hours. Flexible endoscopic evaluation of swallowing (FEES) revealed new-onset bilateral vocal cord palsy as the cause of respiratory distress, which required re-intubation and tracheostomy. The bilateral vocal cord palsy persisted despite continued antitubercular therapy on the follow-up examination. Conclusion Considering the aetiology of infectious meningitis, cranial nerve palsies may be suggestive for tuberculous meningitis as underlying disease given their rarity in other bacterial forms of meningitis. Nevertheless, intracranial involvement of inferior cranial nerves is rare even in this specific entity, as only extracranial lesions of inferior cranial nerves have been reported in tuberculosis. With this report of a rare case of bilateral vocal cord palsy due to intracranial involvement of the vagal nerves, we emphasize the importance of timely initiation of treatment for tuberculous meningitis. This may help to prevent serious complications and associated poor outcome since the response to anti-tuberculosis therapy may be limited.